Laparoscopic Versus Robotic Ventral Hernia Repair – An ACHQC Database 5-Year Analysis - Diego L. Lima; Raquel Nogueira; Joao P. G. Kasakewich; Carlos Andre Balthazar da Silveira; Ana Caroline Dias Rasador; Sharon Phillips; Flavio Malcher (Journal of Abdominal Wall Surgery)
IntroductionTo compare laparoscopic and ventral hernia repair (VHR) in the last 5 years in the United States utilizing the Abdominal Core Health Quality Collaborative (ACHQC) database.Materials and MethodsA retrospective review of prospectively collected data from the ACHQC database was performed to include all adult patients that underwent laparoscopic and robotic VHR in the last 5 years. Univariate analysis was performed to compare outcomes from laparoscopic and robotic-assisted approaches across perioperative and postoperative outcomes.ResultsACHQC database identified 11,096 patients with midline hernias who underwent VHR with mesh. The Laparoscopic group with patients from 2018 to 2023 (LAP) had 2,063 patients, and the robotic group (ROBO) had 9,033 patients. There was no difference in sex, age, BMI, DM, smoking status and COPD between groups. Median hernia width was 4 cm (IQR 2–6) in the ROBO group and 3 cm (IQR 2–5) in the LAP group (p < 0.001). Incisional hernia was higher in the ROBO group 5,259 (58%) versus 1,099 (53%) in the LAP group (p < 0.001). Recurrent hernia was more common in the ROBO group when compared with the LAP group (p < 0.001). Both groups had more permanent synthetic mesh. Retromuscular repair was higher in the ROBO group, 3,201 (37.6%) versus 68 (4.2%) in the LAP group (p < 0.001). The intraperitoneal repair was higher in the LAP group 1,363 (83%) versus 2,925 (34%) in the ROBO group (p < 0.001) Transversus Abdominis Release (TAR) was higher in the ROBO group 1,314 (14.5%) versus 5 (0.2%) in the LAP group (p < 0.001). Fascial closure was higher in the ROBO group (8,649; 96.5% versus 1,359; 67.3% in the LAP group p < 0.001). Regarding mesh fixation, regular suture was higher in the ROBO group 92% versus 61% in the LAP group (p < 0.001). Tacks (p < 0.001) was higher in the LAP group. The ROBO group had more patients with an operative time of 240+ minutes when compared with the LAP group (p < 0.001). There was no difference in 30-days readmission rates, recurrence, reoperation, overall postoperative complications, 30-day SSI, SSO, seroma and SSOPI between the groups.ConclusionThe Robotic approach was associated with more technically challenging ventral hernia repairs with low complication rates over time. However, no differences in postoperative complications were found between the groups.